Comparison of benthic diatom community structures on natural and artificial substrates in marine lake (Adriatic Sea) - Car, Ana; Hafner, Dubravka; Dupčić Radić, Iris; Kaleli, Aydin; Ljubimir, Stijepo; Solak, Cüneyt Nadir (2021)
In this study, the diatoms of three alternative habitats (epilithon, epiphyton and artificial sub-strate) were compared to understand the differences in composition on artificial and natural sub-strates. For this purpose, the samples were collected weekly between 11th August and 2nd Septem-ber 2016 at a sampling site in a shallow marine lake, Mrtvo More (Dead Sea) on Lokrum Island near Dubrovnik (South Adriatic, Croatia). In addition to detailed light microscopic analysis, ultrastructural analysis of benthic diatoms from Lake Mrtvo More was performed for the first time using scanning electron microscopy (SEM). A total of 97 taxa were identified in 12 samples. Cocconeis scutellum Ehrenberg and Halamphora coffeiformis (C.Agardh) Levkov were the most frequent taxa in the samples. Shannon-Wiener diver-sity index (H") values varied from 1.78 (in September on Padina sp.) to 4.52 (in August on glass). According to non-metric multidimensional scaling ordination, there were two groups: epilithon and artificial glass substrate as Group1 and macroalgae as Group2. The results of the analysis showed that the diatom communities developing on artificial sub-strates accurately correspond to the diatom community of a rock substrate and thus can be used as a representative alternative tool for studies of epilithic diatoms in further experiments.
Kako bi se razumjele razlike između naseljavanja na umjetnim i prirodnim podlogama, u ovom istraživanju uspoređivani su sastavi dijatomeja s tri alternativna staništa (epiliton, epifiton i umjetni supstrat). U tu svrhu uzorci su sakupljani tjedno između kolovoza i rujna 2016. na jednoj lokaciji u plitkom morskom jezeru Mrtvo More na otoku Lokrumu kod Dubrovnika (Južni Jadran, Hrvatska). Osim detaljne analize svjetlosnim mikroskopom, po prvi put je provedena i ultrastrukturna analiza bentoskih dijatomeja iz jezera Mrtvo More pomoću elektronske mikroskopije (SEM). U 12 uzoraka identificirano je ukupno 97 vrsta dijatomeja. Vrste Cocconeis scutellum Ehrenberg i Halamphora coffeiformis (C.Agardh) Levkov bile su najčešće vrste u uzorcima. Vrijednosti Shannon-Wiener (H") indeksa varirale su od 1,78 (u rujnu na vrsti Padina sp.) do 4,52 (u kolovozu na staklu). Prema nMDS ordinaciji, razlikuju se dvije skupine zajednica bentoskih dijatomeja: epiliton i umjetna staklena podloga kao Grupa 1 i makroalge kao Grupa 2. Rezultati analize pokazali su da zajednice bentoskih dijatomeja koje se razvijaju na umjetnim podlogama, odgovaraju dijatome-jskoj zajednici kamene podloge i da se stoga mogu koristiti kao reprezentativni alternativni alat za proučavanje epilitskih dijatomeja u daljnjim eksperimentima.
Bibliografija: str. 38-42.
Summary ; Sažetak.
Keywords: Bacillariophyta -- Bioraznolikost -- Bentos -- Dijatomeje -- Morsko jezero; Lokrum -- Jadransko more